Estimasi Kapasitas Dan Titik Berat Pada Pembuatan Kapal Jaring Tradisional Di Galangan Kapal Bagan SiapiApi Kabupaten Rokan Hilir Menggunakan Software Autodesk Inventor 2010 - Pindo Evans Manuel Damanik; Yohanes Yohanes; Muftil Badri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Jaring ship building in Bagan Siapiapi Kabupaten Rokan Hilir Riau in general is traditionally. One example that still use the traditional way is how to determine the capacity and center of gravity. In estimating the capacity and gravity in Bagan Siapiapi Kabupaten Rokan Hilir Riau is not accurate so as to anticipate it, Bagan Siapiapi community change the shape and size of the vessel at the time of testing The purpose of the study to estimate the capacity and center of gravity in Bagan Siapiapi. This research is a study case method that uses a single fishing vessel industry is in Bagan Siapiapi. Jaring’s ships measured ship's main dimensions, construction Linggi, keel construction, joist construction, foundation construction machinery, building construction on the upper deck, and wood density testing, subsequent construction of ships drawn using Autodesk Inventor 2010 software. Capacity and center of gravity jaring ship calculations using Autodesk Inventor 2010 software. From the data processing capacity of jaring Bagan Siapiapi Chart for 7.093 kg and an emphasis on jaring ship Bagan Siapiapi is at position: (1) unloading condition (0,9 mm; 888,5 mm ;-162,5 mm) the front view with the tilt angle of the ship experienced a shaky 89,24o and -84o side view (2) maximum load condition ( 0,7 mm; 976,7 mm; -600,4 mm) the front view with the tilt angle of the ship experienced a shaky -89,8o and side view 80,03o.Keywords: jaring ship, capacity, center of gravity, construction